Pseudo-clefts in Italian talk-in-interaction and in interaction-as-represented - De Cesare, Anna-Maria; De Stefani, Elwys (Lingua, 2022)
This article examines Italian pseudo-clefts (PCs) as documented in diverse settings of interaction (ordinary, institutional, multiparty, etc.), as well as in interactions reported by daily newspapers. After an overview of the grammatical and semantic properties of PCs, mainly based on the literature and Italian grammars, the article empirically analyzes attested PCs from two different vantage points, interactional linguistics and text linguistics. By focusing on two different kinds of data, it (i) provides a fine-grained description of PCs in present-day Italian, and, more specifically, (ii) highlights the differences in PCs occurring in talk-in-interaction vs. journalistic texts, in particular in reported speech. It shows that the way in which linguists conceptualize PCs is largely informed by the specific features of the data considered, such as temporality, sequentiality, and embodiment for talk-in-interaction, and spatiality, hierarchy and textual structures for newspaper articles. Finally, the article provides an overview of the most significant properties of PCs as they appear in both sets of data. It highlights the theoretical and empirical differences between the two frameworks chosen to analyze PCs, and reflects on the heuristic benefits and difficulties in combining different research traditions.